Resin composition and molding including resin composition
Patent Information
- Application Number
- JP2024227435
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0012】 本発明によれば、優れた接着性及びガスバリア性を示す成形体を得ることができる。
Smart Images

Figure 2025031881000005 
Figure 2025031881000001 
Figure 2025031881000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition including an adhesive and at least one layer including the resin composition. It relates to a molded body. [Background technology]
[0002] Packaging materials made of thermoplastic resins for food, beverages, medicines, etc. are used to prevent deterioration of the contents. The purpose is to develop ethylene vinyl alcohol, which has excellent gas barrier properties, aroma retention, and solvent resistance. EVOH copolymers (hereinafter sometimes abbreviated as EVOH) are used in a variety of applications. However, EVOH is hydrophilic, and its gas barrier properties, etc., decrease when it absorbs moisture. Generally, it is laminated with polyolefins such as polyethylene and polypropylene, which have excellent water resistance. It is known to be used in the mid-layers of the body.
[0003] EVOH has many hydroxyl groups in its molecule, making it suitable for use in polyethylene and polypropylene. Its affinity with polyolefins that do not have polar groups is extremely low, and the two generally do not adhere to each other. Therefore, for EVOH, which is difficult to bond with polyolefin, unsaturated carboxylic acid or its derivative Graft-modified ethylene resin compositions grafted with an ethylene glycol graft copolymer (for example, see Patent Documents 1 to 2) ) or ethylene-vinyl acetate copolymer hydrolyzate (see, for example, Patent Document 3) as adhesives. As a result, a method of using it between a polyolefin layer and an EVOH layer has been proposed.
[0004] However, the grafted polysaccharides grafted with the former unsaturated carboxylic acid or its derivatives The ethylene-based resin composition has excellent adhesive properties, but it is highly reactive with EVOH. If the resin is repeatedly mixed or added to EVOH, the viscosity of the resin that remains in the extruder or die increases. As the temperature rises, the product becomes colored and gels, resulting in numerous fish eyes and gels in the product. In addition, the latter ethylene-like substances are mixed in, which reduces the product value. Vinyl acetate copolymer hydrolyzate does not cause coloring or gelation even when repeatedly mixed or added to EVOH. By adding a tackifying resin to the hydrolyzed ethylene-vinyl acetate copolymer, EVOH Although the adhesiveness to the surface is improved, the effect is small and the adhesiveness is not improved by small shocks or abrasions during transportation or use. When rubbed, it often peeled off, and sufficient adhesion was not obtained.
[0005] In addition, as a method for improving adhesion, a thermoplastic resin is used as the adhesive, and Ethylene-vinyl ester copolymers with a vinyl ester content of 5 mol % or more, The thermoplastic resin and the modified ethylene-vinyl ester copolymer are grafted. A method using a hydrolysate of a melt-kneaded product has been proposed (see, for example, Patent Documents 4 and 5). However, this method did not provide sufficient improvement in adhesion.
[0006] In light of this background, we have been developing a new type of EVOH that has excellent adhesiveness and gas barrier properties and can be added to EVOH. Therefore, there has been a demand for adhesives that can be reused repeatedly. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2007-161881 A [Patent Document 2] JP 2000-248128 A [Patent Document 3] JP 2001-200124 A [Patent Document 4] JP 2018-145401 A [Patent Document 5] JP 2020-37604 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above-mentioned circumstances, and is directed to a method for manufacturing a polyethylene or polypropylene-based polymeric polymer film. Resin compositions that combine excellent adhesion to polyolefins such as propylene and excellent gas barrier properties and a molded article including at least one layer containing this resin composition. It is. [Means for solving the problem]
[0009] As a result of intensive research to solve the above problems, the present inventors have discovered a resin containing a specific adhesive. The composition exhibits excellent adhesion to polyolefins and excellent gas barrier properties. It was found that a molded article composed of layers of the resin composition of the present invention can be obtained, and the present invention was completed. This is what I came to do.
[0010] That is, the present invention provides an adhesive (a) that satisfies at least the following (i) to (iii): Parts by weight or more and 60 parts by weight or less of ethylene vinyl alcohol satisfying the following (iv) to (vi): copolymer (b) in an amount of 40 parts by weight or more and 90 parts by weight or less (the total of (a) and (b) is 100 parts by weight or less) The present invention relates to a resin composition comprising: (i) Polyolefin resin (c), vinyl ester resin rather than polyolefin resin (c) Ethylene-vinyl ester copolymers (d) having a vinyl content of 5.00 mol% or more, and A hydrolyzate of a melt-kneaded product containing the modified product (e) grafted with (c) and (d) (ii) A vinyl alcohol content of 0.50 mol% or more and 40.0 mol% or less. (iii) Vinyl ester content is 30.0 mol% or less (iv) Ethylene content is 40 mol% or less (v) The heat of fusion measured by DSC is less than 70 J / g. (vi) A degree of saponification of 70% by weight or more
[0011] The present invention also provides a method for manufacturing a pharmaceutical composition comprising the steps of: or more and 60 parts by weight or less, and an ethylene-vinyl alcohol co-mixture satisfying the following (vi) and (vii): Polymer (b) is 40 parts by weight or more and 90 parts by weight or less (the total of (a) and (b) is 100 parts by weight). The present invention relates to a resin composition comprising: (i) Polyolefin resin (c), vinyl ester resin rather than polyolefin resin (c) Ethylene-vinyl ester copolymers (d) having a vinyl content of 5.00 mol% or more, and A hydrolyzate of a melt-kneaded product containing the modified product (e) grafted with (c) and (d) (ii) A vinyl alcohol content of 0.50 mol% or more and 40.0 mol% or less. (iii) Vinyl ester content is 30.0 mol% or less (vi) A degree of saponification of 70% by weight or more (vii) Ethylene content C2 (mol%) was measured according to ISO 1183-3 Density D EVOH (kg / m 3 ) satisfies the following formula (1): D EVOH <-4.265×C2+1325 (1) Effect of the Invention
[0012] According to the present invention, a molded article exhibiting excellent adhesiveness and gas barrier properties can be obtained. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a diagram showing formulas (1) and (2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The resin composition according to one embodiment of the present invention will be described in detail below.
[0015] The present invention relates to an adhesive (a) that satisfies at least the following (i) to (iii): 60 parts by weight or less of an ethylene-vinyl alcohol copolymer satisfying the following (iv) to (vi): (b) is contained in an amount of 40 parts by weight or more and 90 parts by weight or less (the total of (a) and (b) is 100 parts by weight). The present invention relates to a resin composition characterized by the above. (i) Polyolefin resin (c), vinyl ester resin rather than polyolefin resin (c) Ethylene-vinyl ester copolymer (d) having a vinyl content of 5 mol % or more, and (c) and A hydrolyzate of a melt-kneaded product containing the modified product (e) grafted with (d) (ii) A vinyl alcohol content of 0.50 mol% or more and 40.0 mol% or less. (iii) Vinyl ester content is 30.0 mol% or less (iv) Ethylene content is 40 mol% or less (v) The heat of fusion measured by DSC is less than 70 J / g. (vi) A degree of saponification of 70% by weight or more
[0016] This resin composition is referred to as the first resin composition in contrast to the second resin composition described below. It is also possible.
[0017] The polyolefin resin (c) constituting the adhesive (a) in the present invention is not particularly limited. There is no limit, but it is an α-olefin with 2 to 12 carbon atoms, such as ethylene, propylene, and 1-butene. Homopolymers or copolymers thereof, ethylene and vinyl esters and / or acrylic acid and copolymers with esters.
[0018] Examples of the polyolefin resin (c) include high-pressure low-density polyethylene, high-density polyethylene, and the like. Ethylene, medium density polyethylene, ethylene-1-butene copolymer, ethylene-1-hexene Ethylene / 1-octene copolymer, Ethylene / 4-methyl-1-pentene copolymer Polymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid ester copolymer, ethylene Ethylene-methacrylate copolymers and other ethylene polymers, polypropylene, propylene Polypropylene-ethylene copolymer, propylene-1-butene copolymer, poly-1-butene, poly-1-hexene Polyolefin resins (c) include: They may be used alone or in combination of two or more. Among them, from the viewpoints of moldability and cost, High-pressure low-density polyethylene, ethylene-vinyl ester copolymer, high-density polyethylene , ethylene-1-butene copolymer, ethylene-1-hexene copolymer, polypropylene An ethylene-vinyl acetate copolymer is preferred, and an ethylene-vinyl acetate copolymer is more preferred.
[0019] The method for producing high-pressure low-density polyethylene can be exemplified by high-pressure radical polymerization. Such resins can be conveniently selected from among commercially available products, for example, Petroleum Resin from Tosoh Corporation. It is commercially available under the trade name Trothene. High density polyethylene, ethylene-1-butene copolymer The method for producing the copolymer and the ethylene-1-hexene copolymer is not particularly limited. High, medium and low pressure ion-gravity reactions using Grah-Natta, Phillips and metallocene catalysts Such resins can be conveniently selected from commercially available products. For example, Nipolon Hard, Nipolon-L, Nipolon-Z, and Rumi from Tosoh Corporation. Each is sold under the trade name TACK.
[0020] The production method of ethylene-vinyl acetate copolymer is As long as it is possible, there is no particular limitation, but known high pressure radical polymerization methods and ionic polymerization methods can be used. Examples of polymerization methods include solution polymerization and latex polymerization. Tosoh Corporation is selling the fluoropolymer copolymer under the trade name Ultrathene, while LANXESS is selling the fluoropolymer copolymer under the trade name Ultrathene. It is commercially available under the trade names Levapren and Levamelt.
[0021] Among these, vinyl ester resin (c) of polyolefin resin is preferred because of its excellent sealing properties. Ethylene-vinyl ether having a terephthalate content of 0.50 mol% or more and 10.0 mol% or less. Preferably, it is a ester copolymer, more preferably having a vinyl ester content of 2.00mM. The range is from 0.5 mol% to 8.00 mol%.
[0022] The ethylene-vinyl ester copolymer (d) constituting the adhesive (a) in the present invention is The vinyl ester content is 5.00 mol% or more higher than that of the polyolefin resin (c). It is something.
[0023] Examples of the ethylene-vinyl ester copolymer (d) include ethylene-vinyl acetate copolymer. Copolymer, ethylene-vinyl butyrate copolymer, ethylene-vinyl valerate copolymer, ethylene- Among them, ethylene-vinyl acetate copolymers are the most popular from the viewpoint of cost. A copolymer is preferred.
[0024] In addition, it has excellent compatibility with ethylene-vinyl alcohol copolymer (b) and excellent sealing properties. Therefore, the vinyl ester content of ethylene-vinyl ester copolymer (d) is 12.0 mol % or more and 35.0 mol % or less, and more preferably 20.0 mol % or more and 35.0 mol % or less. The range is 1% or more and 35.0mol% or less.
[0025] Adhesive (a) is a polyolefin resin (c) and an ethylene vinyl ester copolymer The compounding ratio of the component (d) is set to 100% by weight of polyolefin resin ( c) from 5 parts by weight to 95 parts by weight, and ethylene-vinyl ester copolymer (d) from 5 parts by weight and 95 parts by weight or less (the total of (c) and (d) being 100 parts by weight) are preferred. More preferably, the polyolefin resin (c) is 50 parts by weight or more and 90 parts by weight or less, and the ethylene 10 parts by weight or less of styrene-vinyl ester copolymer (d) 50 parts by weight or less (the sum of (c) and (d) The total amount of the polyolefin resin (c) is 100 parts by weight, and the most preferable amount of the polyolefin resin (c) is 70 parts by weight or more and 90 parts by weight or less. parts by weight or less, and ethylene-vinyl ester copolymer (d) is from 10 parts by weight to 30 parts by weight. (The total of (c) and (d) is 100 parts by weight).
[0026] The adhesive (a) in the present invention preferably further contains a compatibilizer (g). The agent (g) is a mixture of polyolefin resin (c) (hereinafter sometimes abbreviated as component (c)) and ethyl acetate. The copolymer (d) (hereinafter sometimes referred to as component (d)) is made compatible with the The compatibilizer (g) is, for example, an ethylene-vinyl ester copolymer. The vinyl ester content of the compatibilizer (g) is higher than that of the component (c), and , preferably lower than that of component (d).
[0027] When the compatibilizer (g) is an ethylene-vinyl ester copolymer, the vinyl ester unit The vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, and vinyl butyrate are Vinyl, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, Aliphatic vinyl esters such as vinyl thearate, aromatic vinyl esters such as vinyl benzoate etc.
[0028] Ethylene-vinyl acetate copolymer is used as the compatibilizer (g) because of its economical advantage. It is preferable to use one type alone or two or more types in combination. and the dispersibility of component (d) is improved, and the gas barrier properties and adhesiveness of the resin composition of the present invention are improved. Therefore, it is preferable to use two or more types of the compatibilizer (g) in combination.
[0029] When the compatibilizer (g) is an ethylene-vinyl ester copolymer, it forms with the compatibilizer (g). The difference in vinyl ester content between component (c) is preferably 1 to 40% by weight, and more preferably or the vinyl ester content difference is 1 to 30% by weight, and most preferably the vinyl ester content difference is It is 1 to 20% by weight.
[0030] When the compatibilizer (g) is an ethylene-vinyl ester copolymer, it forms with the compatibilizer (g). The difference in vinyl ester content between the component (d) is preferably 1 to 40% by weight, and more preferably or the vinyl ester content difference is 1 to 30% by weight, and most preferably the vinyl ester content difference is It is 1 to 20% by weight.
[0031] When two or more types of ethylene-vinyl ester copolymers are used as the compatibilizer (g), The difference in vinyl ester content between the components constituting the solubilizer (g) is 1 to 20% by weight. It is preferable that the content of the amine is 1 to 15% by weight, more preferably 1 to 15% by weight, and most preferably 1 to 10% by weight. be.
[0032] The method for producing the ethylene-vinyl ester copolymer as the compatibilizer (g) is not limited. However, known production methods include high pressure radical polymerization, solution polymerization, and latex polymerization. Resins such as these can be conveniently selected from commercially available products, and are ethylene-vinyl acetate copolymers. Tosoh Corporation has sold Ultrasen and LANXESS K.K. has sold Levapre These are commercially available under the trade names of Levamelt and Revamelt.
[0033] In the case where the adhesive (a) contains a compatibilizer (g), the compounding ratio is determined based on the gas barrier property and adhesive property tendency. From the above viewpoints, the ratio of the compatibilizer (g) to the total of 100 parts by weight of the components (c) and (d) is The amount of the compounding agent is preferably 10 parts by weight or more and 50 parts by weight or less, and more preferably 15 parts by weight or less. The amount of the component (A) is from 1 part by weight to 35 parts by weight.
[0034] The adhesive (a) contains a modified substance (e). Here, the modified substance (e) is a polyolefin resin ( (c) and ethylene-vinyl ester copolymer (d) are grafted. The method for graft-modifying the compound (e) is not particularly limited as long as it is a method capable of graft-modifying the compound. For example, component (c) may contain ethylene and vinyl ester. Component (d) is a method of graft copolymerizing ethylene alone or ethylene and α-olefin. A method of graft copolymerizing fins, in which components (c) and (d) are polymerized in advance and then crosslinked From the viewpoint of productivity, the use of component (c) and component (h) as graft modifiers is preferred. A preferred method is to graft-modify (d) with a crosslinking agent (h). As the catalyst, it is preferable to use an organic peroxide.
[0035] The organic peroxide is not particularly limited as long as the object of the present invention is achieved. For example, Di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butyl 1,1-di(t-butylperoxy)cyclohexane, 2,5 -Dimethyl-2,5-di(t-butylperoxy)hexyne-3,1,3-bis(t-butyl 1,1-bis(t-butylperoxy)-3, 3,5-Trimethylcyclohexane, 1,3-di-(t-butylperoxy)-diisopropyl propylbenzene, n-butyl-4,4-bis(t-butylperoxy)valerate, Dibenzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl Peroxide, t-butyl peroxybenzoate, t-butyl peroxyisopropyl Carbonate, diacetyl peroxide, lauroyl peroxide, t-butyl cumyl peroxide These can be used alone or in combination of two or more. It is possible.
[0036] Among them, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,1 From the viewpoint of reactivity, di(t-butylperoxy)cyclohexane is preferred. In addition to the crosslinking agent (h), triallyl isocyanurate, divinylbenzene, etc. may be used as necessary. A crosslinking assistant such as may be used.
[0037] The amount of crosslinking agent (h) is the same as that of polyolefin resin (c) and ethylene vinyl ester. It is preferably in the range of 0.005 to 1 part by weight based on 100 parts by weight of the total of the polymer (d). This makes it possible for the resin composition of the present invention to have both higher gas barrier properties and higher moldability. It becomes something that is prepared.
[0038] Specific examples of the manufacturing process of the melt-kneaded product containing the modified substance (e) constituting the adhesive of the present invention include: An example is as follows:
[0039] A dry blend of component (c), component (d), compatibilizer (g), and crosslinking agent (h) is extruded. The components (c), (d), (g) and (h) are added to the hopper of the machine. At least a part of the feed may be added from a side feeder, etc. Furthermore, two or more extruders may be used. The components (c), (d) and (g) may be used in succession in a stepwise manner. ) and crosslinking agent (h) are mixed using a Henschel mixer, V blender, ribbon blender, A tumbler or the like may also be used.
[0040] In addition to the above-mentioned components, the adhesive (a) of the present invention may contain, as necessary, a crosslinking assistant, Antioxidants, lubricants, neutralizing agents, antiblocking agents, surfactants, slip agents, etc., usually thermoplastic Additives used in plastic resins and other thermoplastic resins such as polyolefins are added. I don't mind.
[0041] The method for hydrolysis of the molten kneaded material constituting the adhesive in the present invention is not particularly limited. However, from the viewpoint of productivity, it is preferable to directly dehydrate the pellets or powder of the resin composition in an alkali. It is preferable to dissolve the
[0042] The saponification degree of the vinyl ester component of the adhesive (a) of the present invention is 5. % by weight or more, more preferably 5 to 60% by weight, and further preferably 20 to 60% by weight. % by weight, and most preferably in the range of 40 to 60% by weight.
[0043] The vinyl alcohol content of the adhesive (a) in the present invention determines the adhesiveness and ethylene vinyl From the viewpoint of compatibility with the alcohol copolymer (b), 0.50 mol% or more and 40.0 mol % or less, more preferably in the range of 2.00 mol % or more and 20.0 mol % or less. and most preferably in the range of 4.00 mol % or more and 10.0 mol % or less.
[0044] The vinyl ester content of the adhesive (a) in the present invention determines the adhesiveness and the ethylene vinyl ester content. From the viewpoint of compatibility with the alcohol copolymer (b), the content is preferably in the range of 30.0 mol % or less. More preferably, it is in the range of 2.00 mol % or more and 10.0 mol % or less, and most preferably The range is 2.00 mol% or more and 5.00 mol% or less.
[0045] Measured according to JIS K6924-1 (1997) for the adhesive (a) of the present invention From the viewpoint of adhesiveness, the melt mass flow rate (MFR) is in the range of 5 to 50 g / 10 min. The range is preferably 5 to 20 g / 10 min, more preferably 10 to 20 g / 10 min, and most preferably 10 to 20 g / 10 min. The range is 20g / 10min.
[0046] The resin composition of the present invention contains an ethylene-vinyl alcohol copolymer (b). The ethylene content of the vinyl alcohol copolymer (b) is 40 mol % or less, preferably The content of the gas barrier layer in the resin composition of the present invention is 20 mol % or more and 35 mol % or less. The realism is further improved.
[0047] The degree of saponification of the ethylene-vinyl alcohol copolymer (b) is such that it has excellent gas barrier properties. Therefore, it is 70% by weight or more.
[0048] The heat of fusion of such an ethylene-vinyl alcohol copolymer (b) is as follows from the viewpoint of adhesiveness: The maximum permeability is less than 70 J / g, preferably 20 to 65 J / g, and more preferably 30 to 50 J / g. This further improves the adhesiveness of the resin composition of the present invention.
[0049] Here, the heat of fusion is measured by differential scanning calorimetry (hereinafter referred to as "DSC"). Specifically, a measurement pan containing 10 mg of EVOH was used as the measurement sample, and DSC Q20 00 (manufactured by TA Instruments) in a nitrogen atmosphere (flow rate 50 mL / min). DSC measurement was carried out. First, the temperature was raised from room temperature to 250°C at a rate of 80°C / min. The sample was then cooled to -30°C at a rate of 10°C / min and held at -30°C for 5 minutes. After that, the temperature was increased from -30°C to 250°C at a rate of 10°C / min to obtain the desired D Got the SC chart.
[0050] Using the obtained DSC chart, JIS K6922-2 (2018) from 90℃ Endothermic peak in the temperature range up to the extrapolated melting end temperature obtained by analysis using a method based on The heat of fusion was calculated from the above.
[0051] Melt of ethylene-vinyl alcohol copolymer (b) measured according to ISO 1133 The Thomas flow rate (temperature 190°C, load 2.16 kg) is set to 0.1 to 1.5 from the viewpoint of moldability. The preferred range is 100 g / 10 min, and the more preferred range is 0.5 to 50 g / 10 min. It is preferable that the concentration is 1 to 20 g / 10 min.
[0052] Ethylene-vinyl alcohol copolymer (b) was measured according to ISO1183-3. The density is 1190kg / m from the viewpoint of adhesiveness. 3 Less than 1100~1180k is preferable. g / m 3 More preferably, it is 1140 to 1180 kg / m 3 It is most preferable to I wish.
[0053] The method for producing the ethylene-vinyl alcohol copolymer (b) is not particularly limited. For example, For example, a copolymer of ethylene and a fatty acid vinyl ester is produced according to a known method. This is then hydrolyzed to produce an ethylene-vinyl alcohol copolymer. It is possible.
[0054] Ethylene-vinyl alcohol copolymers are also made up of ethylene units and vinyl alcohol units. In addition, small amounts of other structural units may be contained.
[0055] Such resins can be conveniently selected from commercially available products. For example, Kuraray Co., Ltd. They are sold under the trade names of EVAL, Soarnol, and G-Soarnol by Mitsubishi Chemical Corporation. There are.
[0056] The adhesive (a) and the ethylene-vinyl alcohol copolymer ( From the viewpoint of adhesiveness and gas barrier properties, the preferred compounding ratio of adhesive (a) is 10 parts by weight. and ethylene-vinyl alcohol copolymer (b) is 40 parts by weight or more and 90 parts by weight or less. parts by weight or less (the sum of (a) and (b) being 100 parts by weight), more preferably The adhesive (a) is 20 parts by weight or more and 50 parts by weight or less of an ethylene-vinyl alcohol copolymer ( b) in an amount of 50 parts by weight or more and 80 parts by weight or less (the total of (a) and (b) is 100 parts by weight), and most preferably Preferably, the adhesive (a) is 25 parts by weight or more and 40 parts by weight or less, and the ethylene-vinyl alcohol co-polymer is Polymer (b) is 60 parts by weight or more and 75 parts by weight or less (the total of (a) and (b) is 100 parts by weight). Includes.
[0057] The resin composition of the present invention comprises an adhesive (a) and an ethylene-vinyl alcohol copolymer (b The resin composition of the present invention comprises an adhesive (a), an ethylene-vinyl alcohol copolymer, (b) can be mixed with each other. The mixing method is dry blending. For example, the melt-kneading method is a method of mixing each component. There are no particular limitations on the melt kneading device as long as it can uniformly disperse the components. For example, a single screw extruder, a multi-screw extruder, a Banbury mixer, etc. Examples of melt kneading equipment include a pressurized kneader, a rotary roll, and a lab plasto mill. The melting temperature is preferably from the melting point of the ethylene-vinyl alcohol copolymer (b) to about 260°C.
[0058] The resin composition of the present invention can be used in any form, such as pellets or powder. This can be done.
[0059] The resin composition of the present invention may contain other thermoplastic resins as long as the object of the present invention is achieved. Polyolefin resin (k) may be used because of its excellent moldability and adhesiveness. It is preferable that
[0060] Examples of such polyolefin resins (k) include ethylene, propylene, 1-butene, Homopolymers of α-olefins having 2 to 12 carbon atoms or copolymers thereof, ethylene and copolymers of vinyl ester and / or acrylic ester.
[0061] For example, high-pressure low-density polyethylene, high-density polyethylene, medium-density polyethylene, ethylene Ethylene-1-butene copolymer, Ethylene-1-hexene copolymer, Ethylene-1-octene Copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-vinyl acetate copolymer Body, Ethylene-acrylic acid ester copolymer, Ethylene-methacrylic acid ester copolymer Ethylene-based polymers such as polypropylene, propylene-ethylene copolymers, propylene- Propylene-based polymers such as 1-butene copolymers, poly-1-butene, poly-1-hexene, The polyolefin resin (k) may be one of the above. Among them, the high pressure method is preferred from the viewpoint of adhesion and cost. Low density polyethylene, ethylene-vinyl acetate copolymer, high density polyethylene, ethylene- 1-Butene copolymer, ethylene-1-hexene copolymer, polypropylene, propylene- Ethylene copolymers are preferred, and these compositions are most preferred because of their excellent moldability. In addition to the adhesive (a) and the ethylene-vinyl alcohol copolymer (b) constituting the present invention, When mixing other thermoplastic resins, pellets of the resin composition of the present invention and pellets of the thermoplastic resin are mixed. The pellet mixture may be a mixture of pellets in a solid state, but may be extruded using a single screw extruder or a twin screw extruder. Mixtures that are melt-kneaded using a kneader, Banbury mixer, etc. produce products with stable quality. When using a melt kneading device, the melting temperature is The melting point of the polymer to about 260°C is preferred.
[0062] The resin composition of the present invention may further contain, as necessary, an antioxidant, a light stabilizer, an antistatic agent, Additives commonly used in polyolefin resins, such as lubricants and antiblocking agents, are added to the product. It may be added within a range that does not impair the object of the present invention.
[0063] The resin composition of the present invention may be used as a single layer, but the layer may be used as a single layer. From the viewpoint of the property, a layer containing a polyolefin resin (f) is provided on both sides of the layer made of the resin composition. It may also be used as a laminate.
[0064] The polyolefin resin (f) is not particularly limited, and may be, for example, a polyolefin resin produced by a high-pressure method. Low density polyethylene, high density polyethylene, medium density polyethylene, ethylene-1-butene Copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene Ethylene-4-methyl-1-pentene copolymer, ethylene-vinyl acetate copolymer, ethylene-acetone copolymer Ethylene-based copolymers such as acrylic acid ester copolymers and ethylene-methacrylic acid ester copolymers Polymer, polypropylene, propylene-ethylene copolymer, propylene-1-butene copolymer poly(1-butene), poly(1-hexene), poly(4-methyl-1-pentene), etc. .
[0065] The laminate can be used as a component for a blow molded product. The laminate can be suitably used as a blow molded article.
[0066] The laminate can be used as a member constituting a sheet molded product. The laminate can be suitably used as a sheet molded article.
[0067] The laminate can be used as a member constituting a film molded product. The laminate can be suitably used as a film molded article.
[0068] The laminate can be used as a component for an extrusion laminate molding. That is, the laminate can be suitably used as an extrusion laminate molded article having the laminate.
[0069] The resin composition of the present invention can be suitably used as a raw material for injection molding. The resin composition of the present invention can be suitably used as an injection molded article.
[0070] The resin composition of the present invention can be suitably used as a raw material for compression molding. The resin composition of the present invention can be suitably used as a compression molded product.
[0071] The molded article of the present invention can be molded using a conventional molding apparatus. Examples of the methods include extrusion molding, blow molding, sheet molding, injection molding, compression molding, and curing. Die forming, vacuum forming, film forming, extrusion lamination, co-extrusion blow molding, co-extrusion molding Co-extrusion molding, co-extrusion cast molding, co-extrusion inflation molding, co-extrusion laminate molding, Co-injection molding and various co-extrusion molding methods can be used. It can be molded into pipes, blocks, and other shapes, and can be laminated with other materials. By adopting this material, the laminate has other properties such as gas barrier properties, mechanical properties, oil resistance, and weather resistance. It is possible to impart the properties of the material.
[0072] The molded article containing at least the resin composition of the present invention has excellent adhesiveness and gas barrier properties against oxygen and the like. These properties are required for thermoplastic resins such as food, beverages, and pharmaceuticals. It can be suitably used for packaging materials and containers made of such materials.
[0073] The second resin composition according to one embodiment of the present invention will be described in detail below.
[0074] The present invention relates to an adhesive (a) that satisfies at least the following (i) to (iii): 60 parts by weight or less of ethylene-vinyl alcohol copolymer satisfying the following (vi) and (vii): Contains 40 parts by weight or more and 90 parts by weight or less of body (b) (the total of (a) and (b) is 100 parts by weight). The present invention relates to a resin composition comprising: (i) Polyolefin resin (c), vinyl ester resin rather than polyolefin resin (c) Ethylene-vinyl ester copolymer (d) having a vinyl ester content of 5.00 mol % or more, Hydrolyzate of a melt-kneaded product containing the modified product (e) grafted with (c) and (d) (ii) A vinyl alcohol content of 0.50 mol% or more and 40.0 mol% or less. (iii) Vinyl ester content is 30.0 mol% or less (vi) A degree of saponification of 70% by weight or more (vii) Ethylene content C2 (mol%) was measured according to ISO 1183-3 Density D EVOH (kg / m 3 ) satisfies the following formula (1): D EVOH <-4.265×C2+1325 (1)
[0075] Here, the adhesive (a), the polyolefin resin (c), the ethylene-vinyl ester copolymer The polymer (d) and the modified polymer (e) have the same structure as the first resin composition.
[0076] The ethylene content C2 (mol%) is the amount of ethylene contained in the ethylene-vinyl alcohol copolymer (b). The ethylene content in the monomer units contained in the copolymer is
[0077] Density D EVOH (kg / m 3 ) is an ethylene-vinyl alcohol copolymer (b) This is the density at 0°C and can be measured in accordance with ISO1183-3.
[0078] The ethylene-vinyl alcohol copolymer (b) preferably has an ethylene content of C2 and Density D EVOH satisfies the following formula (2). This makes it possible to improve the adhesiveness of the resin composition of the present invention. It will be superior to D EVOH <-4.265×C2+1315 (2) EXAMPLES
[0079] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to these. isn't it.
[0080] (1) Density Density is JIS K6922-1 (1997), JIS K6924-2 (1997 Measured in accordance with ISO 1133. (2) Melt mass flow rate (MFR) MFR is based on JIS K6922-1 (1997), JIS K6924-2 (199 7 years) or was measured in accordance with ISO 1183-3. (3) Vinyl acetate content The vinyl acetate content was measured in accordance with JIS K6924-2 (1997). (4) Saponification degree The degree of saponification was measured before and after saponification in accordance with JIS K6924-2 (1999). Calculations were made using the vinyl acetate content of the adhesive.
[0081] (5) Oxygen permeability The oxygen permeability was measured using the two-type three-layer film (thickness 27 μm) obtained in the examples or the injection molded film. Using a molded body (width 100 mm, length 160 mm, thickness 670 μm), JIS K712 Oxygen permeability (cc / m 2 24 hours atm) For injection molded articles, the value was converted to a value for a thickness of 600 μm. The measured oxygen permeability (cc / m 2 ·24 hours·atm) is 100 or more, ×, less than 100, 10 or more, △, less than 10, 5.0 or less Above 5.0 is marked with ○, below 5.0 is marked with ◎. Oxygen permeability (cc / m 2 ·24 hours·atm) 100 The gas barrier property was judged to be good when the measured value was less than 100%.
[0082] (6)Seal strength / adhesion The seal strength of the two-type three-layer film was measured by dividing the two-type three-layer film obtained in the example by a width of 100 mm. Cut out two pieces of film with a length of 100 mm and place the inner layers of the film together and seal them with a heat seal tester. Using TP-701B (manufactured by Tester Sangyo Co., Ltd.), set temperature to 130℃, double-sided heating, air Pressure 0.2MPa, sealing time 1 second, heating with a seal bar 10mm wide and 300mm long. The test specimen was cut to a width of 15 mm and placed in a tensile testing machine, Tensilon RTE- 1210 (Orientec Co., Ltd.) was used, and the tensile speed was 300 mm / min., and the conditions for T-type peeling were A peel test was carried out to measure the seal strength (N / 15 mm). The seal strength of the injection molded product was obtained according to the example (width 100 mm, length 150 mm, Thickness 670μm) and PET 12μm, anchor coating agent, PE 25μm are layered in that order. The PET / PE substrate (manufactured by Howa Sangyo Co., Ltd.) was cut into pieces with a width of 100 mm and a length of 100 mm. Cut out the molded product, put the PE side of the PET / PE base material on top of the injection molded product, and test it with the heat seal tester TP-7. 01B (manufactured by Tester Sangyo Co., Ltd.) was used, with the temperature set at 160°C, and one-sided heating (PET / PE base) material side), air pressure 0.2MPa, sealing time 2 seconds, width 10mm, length 300mm The test pieces were cut to a width of 15 mm and placed in a tensile tester. A shiron RTE-1210 (Orientec Co., Ltd.) was used at a tensile speed of 300 mm / min. A peel test was conducted at a peel angle of 180° to measure the seal strength (N / 15 mm). Regarding adhesiveness, the seal strength (N / 15mm) of the 2nd type 3-layer film is less than 5.0, which is x. 5.0 or more but less than 6.0 is △, 6.0 or more but less than 7.0 is 〇, and 7.0 or more is ◎. If the seal strength (N / 15mm) of the injection molded product is less than 4.5, it is judged as "X", and if it is 4.5 or more but less than 5.0, it is judged as "X". △, 5.0 or more but less than 5.5, 〇, 5.5 or more, ◎. Adhesion was judged to be good when the strength (N / 15 mm) was equal to or greater than the strength judged as △.
[0083] The manufacturing method for each adhesive is shown below.
[0084] [Method of manufacturing adhesive A1] Polyolefin resin (C) with MFR of 45g / 10min and density of 924kg / m 3 High-pressure low-density polyethylene (manufactured by Tosoh Corporation, product name Petrothene 209) (C1) 75 parts by weight of ethylene-vinyl ester copolymer (D) having an MFR of 70 g / 10 minute, density 968kg / m 3 The vinyl acetate content was 42.0% by weight (19.1 mol%). An ethylene-vinyl acetate copolymer (Ultrathene 760, manufactured by Tosoh Corporation) (D 1) 25 parts by weight, and an organic peroxide (manufactured by NOF Corp., trade name Perhexa C) (H1) The mixture was dry-blended at a ratio of 0.1 parts by weight and then used in a twin-screw extruder TEX25αIII (Made in Japan) (manufactured by Kosho) was used, and the conditions were resin temperature 190°C, rotation speed 150 rpm, and discharge rate 10 kg / hour. The sample was melted and kneaded in a 7% by weight sodium hydroxide solution to obtain a pellet-shaped sample. Hydrolysis treatment was performed in a thorium methanol solution at 45°C, and the saponification degree was 50% by weight. MF R is 28g / 10min, vinyl alcohol content is 1.84mol%, vinyl ester content is An adhesive (A1) having a molecular weight of 1.84 mol % was obtained.
[0085] [Method of manufacturing adhesive A2] Polyolefin resin (C) with MFR of 14g / 10min and density of 935kg / m 3 Ethylene-vinyl acetate copolymer with a vinyl acetate content of 15.0% by weight (5.43 mol%) Polymer (manufactured by Tosoh Corporation, trade name Ultrathene 625) (C2) 70 parts by weight, ethylene Vinyl ester copolymer (D) is 30x ethylene-vinyl acetate copolymer (D1). The adhesive (A1) was produced by the same method as that for producing the adhesive (A1), except that the amount of the adhesive (A1) was changed to 50 parts by weight. %, MFR is 12g / 10min, vinyl alcohol content is 4.45mol%, vinyl ester content is 1.0mol%, An adhesive (A2) with a terephthalate content of 4.45 mol % was obtained.
[0086] [Method of manufacturing adhesive A3] Polyolefin resin (C) with MFR of 30g / 10min and density of 935kg / m 3 Ethylene-vinyl acetate copolymer with a vinyl acetate content of 15.0% by weight (5.43 mol%) Polymer (C3) 85 parts by weight, ethylene-vinyl ester copolymer (D), MFR is 3g / 10min, density is 1000kg / m 3 , vinyl acetate content 50.0% by weight (24. 6 mol%) ethylene-vinyl acetate copolymer (manufactured by LANXESS AG, product name: REVAPO 15 parts by weight of Ren 500 (D2), as a compatibilizer (G), MFR of 20 g / 10 min. Density 940kg / m 3 , the vinyl acetate content is 20.0% by weight (7.53 mol%) Ethylene-vinyl acetate copolymer (Tosoh Corporation, product name Ultrathene 633) was added for 25 minutes. 0 parts by weight, MFR 18g / 10min, density 949kg / m 3 , vinyl acetate content 28. 0% by weight (11.2 mol%) of ethylene-vinyl acetate copolymer (Tosoh Corporation, Product name: Ultrasen 710) 25.0 parts by weight, MFR 30g / 10min, density 954 kg / m 3 Ethylene / acetic acid with a vinyl acetate content of 32.0% by weight (13.3 mol%) 25.0 parts by weight of vinyl acetate copolymer (manufactured by Tosoh Corporation, trade name Ultrathene 750), FR is 70g / 10min, density is 968kg / m 3 , vinyl acetate content 42.0% by weight (1 9.1 mol%) ethylene-vinyl acetate copolymer (manufactured by Tosoh Corporation, trade name Ult 25.0 parts by weight of a resin composition (G1, MFR 30 g / 10 min, density 100%) degree953kg / m 3 , vinyl acetate content 30.5 wt% (12.5 mol%)) to 30.0 The adhesive (A1) was produced in the same manner as in the production method of the adhesive (A1), except that the saponification degree was 46 parts by weight. %, MFR is 14g / 10min, vinyl alcohol content is 4.00mol%, vinyl ester An adhesive (A3) having a vinyl content of 4.69 mol % was obtained.
[0087] [Manufacturing method of adhesive A4] As the polyolefin resin (C), 75% by weight of ethylene-vinyl acetate copolymer (C3) was used. Part (D) is an ethylene-vinyl ester copolymer with a MFR of 4 g / 10 min and a density of 1 100kg / m 3 , ethylene having a vinyl acetate content of 80.0% by weight (56.6 mol%) 200 ml of vinyl acetate copolymer (manufactured by Lanxess AG, trade name Levaprene 800) (D3) 5 parts by weight, as a compatibilizer (G), MFR 160 g / 10 min, density 936 kg / m 3 Ethylene-vinyl acetate copolymer with a vinyl acetate content of 20.0% by weight (7.53 mol%) Polymer (Tosoh Corporation, trade name Ultrathene 680) 33.3 parts by weight, MFR 30 g / 10 min, density 954 kg / m 3 , vinyl acetate content 30.0% by weight (13.3 mo 1%) ethylene-vinyl acetate copolymer (manufactured by Tosoh Corporation, product name Ultrasen 75 0) 33.4 parts by weight, MFR 3g / 10min, density 1000kg / m 3 , vinyl acetate Ethylene-vinyl acetate copolymer (Ran) with a content of 50.0% by weight (24.6 mol%) A resin composition (G2) consisting of 33.3 parts by weight of Levaprene 500 (manufactured by Xess Co., Ltd.) , MFR24g / 10min, density 963kg / m 3 , vinyl acetate content 34.0% by weight (14 The same manufacturing method as for adhesive (A1) was used except that the amount of 0.4 mol%) was 20.0 parts by weight. This resulted in a degree of saponification of 30% by weight, MFR of 11g / 10min, and vinyl alcohol content of 3. 94 mol % and a vinyl ester content of 9.19 mol %.
[0088] [Manufacturing method of adhesive A5] Saponification was performed by changing the hydrolysis treatment time in 7% by weight sodium hydroxide methanol solution. The adhesive (A3) was produced by the same method as that of the adhesive (A3) except that the saponification degree was adjusted to 30. %, MFR is 15g / 10min, vinyl alcohol content is 2.61mol%, vinyl ether content is 2.61mol%, An adhesive (A5) with a steric content of 6.08 mol % was obtained.
[0089] [Method of manufacturing adhesive A6] The following polyolefin resin (C) was used as ethylene-vinyl acetate copolymer (C2). The other adhesives are manufactured in the same manner as the adhesive (A3), with a saponification degree of 46% by weight and an MFR of 8. g / 10 min, vinyl alcohol content 4.00 mol%, vinyl ester content 4.69 Thus, an adhesive (A6) having a molecular weight of 1.0 mol % was obtained.
[0090] [Method of manufacturing adhesive A7] The adhesive (A3) was produced in the same manner as the adhesive (A3), except that no hydrolysis treatment was performed. Saponification degree: 0.00% by weight, MFR: 12g / 10min, vinyl alcohol content: 0.00 mol %, and an adhesive (A7) having a vinyl ester content of 8.69 mol % was obtained.
[0091] [Method of manufacturing adhesive A8] The manufacturing method was the same as that of adhesive (A3), except that the crosslinking agent (H1) was not added. As a result, the saponification degree is 46% by weight, the MFR is 23g / 10min, and the vinyl alcohol content is 4.0 0 mol % and vinyl ester content of 4.69 mol %. This adhesive (A8) is made of polyolefin resin (C) and ethylene vinyl ester copolymer. The modified product (E) to which the polymer (D) has been grafted is not included.
[0092] [Table 1]
[0093] Example 1 Adhesive (A1) was used as adhesive (A) and ethylene-vinyl alcohol copolymer (B) The MFR is 2.0g / 10min and the density is 1160kg / m 3 , ethylene content is 32 mol %, saponification degree 100% by weight, and heat of fusion 46 J / g. Copolymer (manufactured by Kuraray Co., Ltd., product name EVAL SP482B) (B1) was mixed with polyolefin (F) MFR is 2.0g / 10min, density is 910kg / m 3 Ethylene 1- 70% by weight of hexene copolymer (manufactured by Tosoh Corporation, product name Nipolon-Z, HF210K, Part, MFR 2.0g / 10min, density 922kg / m 3 High-pressure low-density polyethylene Dry blend was added to the mixture so that the total weight of the mixture was 30 parts by weight. The polyolefin resin composition (MFR 2.0 g / 10 min, density 914 kg / m 3 , F1) was used. First, 25 parts by weight of (A1) and 75 parts by weight of (B1) are dry blended, A 40mmφ single-screw extruder (Placo Corporation) was used, and the resin temperature was set at 200°C and the rotation speed was set at 25 rpm. The mixture was melt-kneaded at 7.0 kg / hour in a 300-series oven and discharged at 7.0 kg / hour to obtain a pellet-shaped EVOH-based resin composition. Got it. Next, a three-layer cast molding machine (Pla- to Co., Ltd.) with screws of 32 / 25 / 25 mm diameter was used. The intermediate layer was formed by an extruder (25 mm diameter) made by the STICK Engineering Research Institute. and (B1) is 75 parts by weight. (F1) was fed to two extruders (32 mmφ and 25 mmφ) and the middle layer was heated to 210°C and The inner and outer layers are extruded at a temperature of 180°C and taken up at a take-up speed of 16 m / min. (F1) / EV Two types of 3-component resins with a thickness of 27 μm, each having a thickness of 11 μm / 5 μm / 11 μm. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 2.
[0094] Example 2 The same procedure as in Example 1 was repeated except that adhesive (A2) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 2.
[0095] Example 3 The same procedure as in Example 1 was repeated except that adhesive (A3) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 2.
[0096] Example 4 The same procedure as in Example 1 was repeated except that adhesive (A4) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 2.
[0097] Example 5 The same procedure as in Example 1 was repeated except that adhesive (A5) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 2.
[0098] Example 6 The same procedure as in Example 1 was repeated except that adhesive (A6) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 2.
[0099] Example 7 As an EVOH-based resin composition, 20 parts by weight of adhesive (A3) and ethylene vinyl alcohol were used. A two-kind, three-layer film was prepared in the same manner as in Example 3, except that the amount of the copolymer (B1) was 80 parts by weight. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 2.
[0100] Example 8 As an EVOH-based resin composition, 40 parts by weight of adhesive (A3) and ethylene vinyl alcohol were used. A two-kind, three-layer film was prepared in the same manner as in Example 3, except that the amount of the copolymer (B1) was 60 parts by weight. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 2.
[0101] Example 9 Ethylene-vinyl alcohol copolymer (B) has an MFR of 1.9 g / 10 min. The hydroxyl content is 33 mol%, the degree of saponification is 100% by weight, and the density is 1180 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer with a strength of 62 J / g (Mitsubishi Chemical Corporation product) The same procedure as in Example 3 was used except that Soarnol GC3304B (B2) was used. The obtained two-type three-layer film was used to measure the oxygen permeability and seal strength. The results are shown in Table 2.
[0102] Example 10 Ethylene-vinyl alcohol copolymer (B) has an MFR of 1.7 g / 10 min. The hydroxyl content is 32 mol%, the degree of saponification is 100% by weight, and the density is 1180 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer (product name: Eva, manufactured by Kuraray Co., Ltd.) with a thermal conductivity of 68 J / g A two-type three-layer filter was prepared in the same manner as in Example 3, except that the filter J171B) (B3) was used. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 2.
[0103] [Table 2]
[0104] Comparative Example 1 Ethylene-vinyl alcohol copolymer (B) has an MFR of 1.7 g / 10 min. The hydroxyl content is 32 mol%, the degree of saponification is 100% by weight, and the density is 1190 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer (product name: Eva, manufactured by Kuraray Co., Ltd.) with a thermal conductivity of 70 J / g A two-type three-layer filter was prepared in the same manner as in Example 1, except that the filter F171B) (B4) was used. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 3. The adhesion was poor.
[0105] Comparative Example 2 The same procedure as in Example 2 was repeated except that (B4) was used as the ethylene-vinyl alcohol copolymer (B). A two-type three-layer film was obtained by the same method as described above. The obtained two-type three-layer film was used to measure the oxygen permeability. The adhesion and seal strength were evaluated, and the results are shown in Table 3. The adhesion was poor.
[0106] Comparative Example 3 The same procedure as in Example 3 was repeated except that (B4) was used as the ethylene-vinyl alcohol copolymer (B). A two-type three-layer film was obtained by the same method as described above. The obtained two-type three-layer film was used to measure the oxygen permeability. The adhesion and seal strength were evaluated, and the results are shown in Table 3. The adhesion was poor.
[0107] Comparative Example 4 Ethylene-vinyl alcohol copolymer (B) has an MFR of 1.7 g / 10 min. The hydroxyl content is 44 mol%, the degree of saponification is 100% by weight, and the density is 1140 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer (manufactured by Kuraray Co., Ltd., product name: Eva) with a thermal conductivity of 64 J / g A two-type three-layer filter was prepared in the same manner as in Example 3, except that the filter E171B) (B5) was used. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 3. The adhesion was poor.
[0108] Comparative Example 5 Ethylene-vinyl alcohol copolymer (B) has an MFR of 8.5 g / 10 min. The hydroxyl content is 35 mol%, the degree of saponification is 100% by weight, and the density is 1180 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer (manufactured by Kuraray Co., Ltd., product name: Eva) with a thermal conductivity of 76 J / g A two-type three-layer filter was prepared in the same manner as in Example 3, except that the 2-type three-layer filter C109B) (B6) was used. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 3. The adhesion was poor.
[0109] Comparative Example 6 The same procedure as in Example 1 was repeated except that adhesive (A7) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 3. The adhesion was poor.
[0110] Comparative Example 7 The same procedure as in Example 1 was repeated except that adhesive (A8) was used instead of adhesive (A). The oxygen permeability and seal strength of the obtained two types of three-layer films were evaluated. The results are shown in Table 3. The adhesion was poor.
[0111] Comparative Example 8 A two-type three-layer film was prepared in the same manner as in Example 1, except that the adhesive (A) was not added. The obtained two-kind three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 3. The adhesion was poor.
[0112] Comparative Example 9 As an EVOH-based resin composition, 65 parts by weight of adhesive (A3) and ethylene vinyl alcohol were used. A two-kind, three-layer film was prepared in the same manner as in Example 3, except that the amount of the copolymer (B1) was 35 parts by weight. The obtained two-type three-layer film was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 3. The gas barrier properties were poor.
[0113] [Table 3]
[0114] Example 11 Adhesive (A3) was used as adhesive (A) and ethylene-vinyl alcohol copolymer (B) Ethylene-vinyl alcohol copolymer (B1) was used as the polyolefin (K) and MF R is 8g / 10min, density is 919kg / m 3 High-pressure low-density polyethylene (Tosoh The product used was Petrothene 203) (K1) manufactured by Petroleum Corporation.
[0115] First, 42.9 parts by weight of (A3), 57.1 parts by weight of (B1), and 42.9 parts by weight of (K1). The mixture was dry-blended to obtain the desired ratio, and then extruded using a Labo Plastomill 4C150 equipped with a twin-screw extruder. (manufactured by Toyo Seiki Co., Ltd.) was used, and the resin temperature was 200°C, the rotation speed was 100 rpm, and the discharge amount was 2.5 The mixture was melt-kneaded at a temperature of 100° C. / hour to obtain a pelletized EVOH-based resin composition. Next, the resin temperature was measured using an injection molding machine MD100Xi2.7 (manufactured by Ube Industries Machinery Co., Ltd.). EVOH-based resin composition obtained under conditions of 220℃, injection pressure of 200MPa, and mold temperature of 50℃ The resulting composition was injection molded. The oxygen permeability and seal strength of the obtained injection molded article were evaluated. The results are shown in Table 4.
[0116] Example 12 Injection molding was performed in the same manner as in Example 11, except that (A4) was used as the adhesive (A). The obtained injection molded article was used to evaluate the oxygen permeability and the seal strength. The results are shown in Table 1. Shown in 4.
[0117] Example 13 The same procedure as in Example 1 was repeated except that (B3) was used as the ethylene-vinyl alcohol copolymer (B). An injection molded article was obtained by the same method as in 1. The oxygen permeability and the symmetry were measured using the obtained injection molded article. The strength of the bond was evaluated, and the results are shown in Table 4.
[0118] Example 14 As an EVOH-based resin composition, 37.5 parts by weight of adhesive (A3) and ethylene vinyl alcohol were used. 62.5 parts by weight of coal copolymer (B1) and 25.0 parts by weight of polyolefin (K1) Except for the above, an injection molded article was obtained in the same manner as in Example 11. The oxygen permeability and seal strength were evaluated, and the results are shown in Table 4.
[0119] Example 15 Injection molding was performed in the same manner as in Example 14, except that (A4) was used as the adhesive (A). The obtained injection molded article was used to evaluate the oxygen permeability and the seal strength. The results are shown in Table 1. Shown in 4.
[0120] Comparative Example 10 The same procedure as in Example 1 was repeated except that (B6) was used as the ethylene-vinyl alcohol copolymer (B). An injection molded article was obtained by the same method as in 1. The oxygen permeability and the symmetry were measured using the obtained injection molded article. The bond strength was evaluated, and the results are shown in Table 4. The adhesiveness was poor.
[0121] Comparative Example 11 Ethylene-vinyl alcohol copolymer (B) has an MFR of 5.5 g / 10 min. The hydroxyl content is 44 mol%, the degree of saponification is 100% by weight, and the density is 1140 kg / m 3 , heat of fusion Ethylene-vinyl alcohol copolymer (manufactured by Kuraray Co., Ltd., product name: Eva) with a thermal conductivity of 64 J / g An injection molded article was prepared in the same manner as in Example 11, except that the injection molding material E105B) (B7) was used. The obtained injection molded article was used to evaluate the oxygen permeability and seal strength. The results are shown in Table 4. The adhesion was poor.
[0122] Comparative Example 12 The same procedure as in Example 1 was repeated except that (B6) was used as the ethylene-vinyl alcohol copolymer (B). An injection molded article was obtained by the same method as in 2. The oxygen permeability and the symmetry were measured using the obtained injection molded article. The bond strength was evaluated, and the results are shown in Table 4. The adhesiveness was poor.
[0123] [Table 4]
[0124] The ethylene content C2 (mol %) and density D EVOH (kg / m 3 The relationship between the two is shown in Figure 1. As shown in this figure, Example 10 (or Example 13) which satisfies formula (1) is different from Comparative Example 3 which does not satisfy formula (1). and 4 (or Comparative Examples 10 and 11). Furthermore, the formula (2) is satisfied. Example 3 (or Example 11) has better adhesion.
[0125] Regarding the slope of formula (1) and formula (2), C2 is 27 mol%, D EVOH 1 210kg / m 3 Ethylene-vinyl alcohol copolymer (manufactured by Kuraray Co., Ltd.) EVAL L171B), C2 is 32mol%, D EVOH is 1190kg / m 3 It is Styrene-vinyl alcohol copolymer (B4), C2 is 35 mol%, D EVOH 118 0kg / m 3 Ethylene-vinyl alcohol copolymer (B6), C2 is 38 mol% , D EVOH is 1170kg / m 3 Ethylene-vinyl alcohol copolymer (Co., Ltd.) Kuraray (product name: EVAL H171B), C2 is 44 mol%, D EVOH is 1140k g / m 3 Ethylene-vinyl alcohol copolymer (B5), C2 is 48 mol%, D EVOH is 1120kg / m 3 Ethylene-vinyl alcohol copolymer (Clark Corporation) C2 and D of EVAL G156B (product name) EVOH The correlation was calculated from the above. [Industrial Applicability]
[0126] The resin composition of the present invention can be used for molded articles that require sealing properties and gas barrier properties. In particular, it is suitable for use in molded articles used as packaging materials for foods, beverages, medicines, etc. can be done.
Claims
1. The resin composition comprises 10 to 60 parts by weight of an adhesive (a) that satisfies at least the following (i) to (iii), and 40 to 90 parts by weight of an ethylene-vinyl alcohol copolymer (b) that satisfies the following (vi) to (vii) (the total of (a) and (b) being 100 parts by weight): (i) a hydrolysate of a melt-kneaded product containing a polyolefin resin (c), an ethylene-vinyl ester copolymer (d) having a vinyl ester content 5.00 mol % or more higher than that of the polyolefin resin (c), and a modified product (e) in which (c) and (d) are grafted (ii) Vinyl alcohol content is 0.50 to 40.0 mol% (iii) Vinyl ester content is 30.0 mol% or less (vi) a degree of saponification of 70% by weight or more (vii) Ethylene content C 2 (mol%) and density D measured according to ISO1183-3 EVOH (kg / m 3 ) satisfies the following formula (1): D EVOH <-4.265×C 2 +1325 (1)
2. 2. The resin composition according to claim 1, wherein the polyolefin resin (c) is an ethylene-vinyl ester copolymer having a vinyl ester content of 0.50 mol % or more and 10.0 mol % or less.
3. The resin composition according to claim 1 or 2, wherein the ethylene-vinyl ester copolymer (d) has a vinyl ester content of 12.0 mol % or more and 35.0 mol % or less.
4. The resin composition according to any one of claims 1 to 3, wherein the adhesive (a) has a melt mass flow rate measured in accordance with JIS K6924-1 (1997) of 5 g / 10 min or more and 50 g / 10 min or less.
5. A laminate comprising a layer made of the resin composition according to claim 1 and layers containing a polyolefin resin (f) laminated on both sides of the layer made of the resin composition.
6. A blow molded article comprising at least the laminate according to claim 5.
7. A sheet molded article comprising at least the laminate according to claim 5.
8. A film molded article comprising at least the laminate according to claim 5.
9. An extrusion laminate molded article comprising at least a substrate layer and the laminate according to claim 5.
10. An injection-molded article comprising at least the resin composition according to any one of claims 1 to 4.
11. A compression molded product comprising at least the resin composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Adhesive, adhesive resin composition and laminate comprising same
WO2017199985A1
Spout fitted with pull ring
JP2000248128A
Fuel container
JP2001200124A
Polyethylenic molding material
JP2007161881A
Resin composition and laminate comprising the same
JP2018145401A